Simple adaptive control method for mitigating the seismic responses of coupled adjacent buildings considering parameter variations. (1st May 2019) - Al-Fahdawi, Omar A.S.; Barroso, Luciana R.; Soares, Rachel W.
Highlights: Classical controllers perform poorly in the presence of uncertainty. Simple Adaptive Controller (SAC) deals quite well with the parameter variations. MR damper is more reliable than the Hydraulic Actuator. Connecting buildings is an effective strategy for mitigating seismic responses. Abstract: The effectiveness of using the simple adaptive control method in the presence of noise and parameter variations in mitigating the seismic structural responses of a coupled buildings structure is studied. The advantage of using the adaptive controller is that it can deal with any change in the dynamic characteristics of structural systems during their lifetime. In the current study, the change in the structural characteristics is reflected as a reduction in the system's mass and stiffness as an outcome of the damage potential in the two buildings under seismic excitations. The coupled system is formed of two buildings modeled as shear-type models having different heights and connected at multiple levels with control devices. The effectiveness of different actuators is explored using the magneto-rheological damper for semi-active control and the hydraulic actuator for active control. A suite of five major earthquakes are chosen as external excitations to perform the dynamic analysis in the time domain. The performance of the adaptive controller is compared with different control strategies such as LQR, and Lyapunov theory-based algorithm. The results show that using the adaptive controller to drive the control devices connecting two adjacent buildings is effective in alleviating the seismic responses. Moreover, the proposed control scheme is more promising for dealing with the structural parameter variations during seismic events than the LQR and Lyapunov theory-based algorithms.